2017
DOI: 10.1111/resp.13147
|View full text |Cite
|
Sign up to set email alerts
|

History of pulmonary tuberculosis affects the severity and clinical outcomes of COPD

Abstract: Background and objective: Although an association between pulmonary tuberculosis (TB) and chronic obstructive pulmonary disease (COPD) has been suggested, studies on the effect of TB in COPD patients have not been conducted. We aimed to investigate the severity and clinical outcomes of COPD in patients with and without a history of TB. Methods: We retrospectively reviewed the data of 1784 patients with COPD in the Korean COPD Subtype Study cohort collected from December 2011 to January 2017 and followed up for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
(42 reference statements)
1
18
0
Order By: Relevance
“…A self-reported history of tuberculosis was associated with both airflow obstruction and spirometric restriction in the multicentre, cross-sectional, general population-based Burden of Obstructive Lung Disease study (4). Other studies also indicated that history of previous tuberculosis was associated with more severe form of COPD, evaluated by CAT scores, lung function, mortality, and exacerbation prevalence (6,(34)(35)(36). However, the cellular and molecular mechanisms underlying the interplay between Mtb and CS exposure in the pathogenesis or progression of COPD are largely unknown.…”
Section: Discussionmentioning
confidence: 97%
“…A self-reported history of tuberculosis was associated with both airflow obstruction and spirometric restriction in the multicentre, cross-sectional, general population-based Burden of Obstructive Lung Disease study (4). Other studies also indicated that history of previous tuberculosis was associated with more severe form of COPD, evaluated by CAT scores, lung function, mortality, and exacerbation prevalence (6,(34)(35)(36). However, the cellular and molecular mechanisms underlying the interplay between Mtb and CS exposure in the pathogenesis or progression of COPD are largely unknown.…”
Section: Discussionmentioning
confidence: 97%
“…Some uncertainty remains regarding whether there is a causal relationship between prior pulmonary TB and COPD. However, patients with pulmonary TB have fairly marked destruction of the lung structure, and previous studies have found that patients with TB have faster lung function decline and meet the diagnostic criteria for COPD more than those without TB (49,50). As a result, we believe that prior TB is a risk factor for COPD.…”
Section: Figurementioning
confidence: 99%
“…While the sizeable protective effects of metformin in the above‐mentioned studies suggest a potential role of the drug as host‐directed therapy in the treatment of latent TB infection and active TB, randomized trials are need to delineate its exact role(s) before introduction into clinical practices . Park et al retrospectively reviewed the data of 1784 patients with chronic obstructive pulmonary disease (COPD) in the Korean COPD Subtype Study cohort . The COPD assessment test (CAT) scores, total St George's Respiratory Questionnaire for COPD (SGRQc) scores and exacerbation prevalence were significantly higher, and lung function was significantly poorer in COPD patients with prior TB than those without, both at the baseline and on follow‐up over 3 years.…”
Section: Tuberculosismentioning
confidence: 99%